(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
In modern times, the fundamental ideas of heuristic methods and heuristic search systems are being studied, with the aim of their further application in various spheres of human activity, including in the process of training specialists in pedagogy. Learning using algo-heuristic methods is not limited only to the acquisition of knowledge, skills and abilities, but also focuses on the internal motivations of learning, ensuring the student’s self-development and self-education. Naturally, learning using algo-heuristic methods cannot completely replace traditional learning; however, it can and should be used as a supplement to traditional methods to develop the learner’s creative abilities. The learner should be given the opportunity to feel like a full participant in the learning process, when he is not forced to acquire knowledge, but is allowed to acquire it independently, even through trial and error. After all, many great discoveries were made completely by chance. Learning using these methods is based on certain principles. Personal goal-setting of the learner, selection of meta-subject bases of educational content, teaching productivity, priority of the learner’s educational product, situational learning, the ability to conduct effective dialogue, form skills, act in an uncertain situation, set an educational goal, achieve it, draw up a plan and find various tricks for solving problems - that is, the methods of algo-heuristics are a set of logical techniques and methodological rules of theoretical research and the search for truth - methods of teaching and upbringing that contribute to the development of individual ingenuity and activity.